Method for preparing formed body for water purification
By mixing natural mineral extract with titanium dioxide nano powder and immersing it in the tissue of plastic raw materials, the molded body is prepared, which solves the problem of difficult to reduce algae bloom phenomenon, and effectively purify water quality and algae bloom inhibition, and has the advantages of low cost and environmental protection.
Patent Information
- Application Number
- CN202410427201.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-28
- Filing Date
- 2024-04-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-04-10
AI Technical Summary
The prior art is difficult to effectively reduce algae bloom phenomenon, and the traditional methods are costly and have the risk of secondary environmental damage.
By preparing a natural mineral extract and mixing it with a titanium dioxide nano powder with photocatalyst action, a natural mineral-photocatalyst aqueous solution is formed, and then it is impregnated into the tissue of the plastic raw material, and a molded body is prepared and placed in the water surface or water.
This method can not only adsorb and decompose organic matter in water, block the reproduction of bacteria and molds, but also effectively reduce algae blooms, and is low in cost and has good environmental protection.
Smart Images

Figure CN118304851B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a molded body for water purification, and more specifically, to a method for preparing a molded body for water purification as follows, wherein a natural mineral-photocatalyst aqueous solution prepared in an environmentally friendly manner and containing titanium dioxide (TiO2) nanopowder having a photocatalytic effect is dispersed in a natural mineral extract solution, and is impregnated into the interior of the structure of a plastic raw material, thereby adsorbing and decomposing organic matter contained in water from lakes or reservoirs, lotus ponds, rivers, aquariums, aquaculture farms, swimming pools, water treatment plants, etc., blocking the reproduction of bacteria and molds, and reducing algal blooms. Background Art
[0002] As a result of rapid industrialization and urbanization, the inflow of organic matter, nitrogen, phosphorus, etc. from human pollution sources such as domestic sewage, industrial wastewater, and agricultural and livestock wastewater continues to increase, and water pollution is therefore regarded as a major problem in society.
[0003] Regarding this water quality ecosystem, the self-purification capacity of the ecosystem to purify pollution sources with the help of natural forces has exceeded the critical point. This may vary depending on the organic matter content of the pollution source flowing in, the size of the river, the flow rate and the weather, but recently the algal bloom phenomenon has caused serious problems in the use of water resources.
[0004] Generally speaking, algal bloom refers to the phenomenon that green algae or blue algae, which are plant plankton, grow in large quantities in eutrophic lakes or slow-flowing rivers, turning the water green. If the surface of such water bodies is covered with green algae, sunlight is blocked from entering the water, and additional dissolved oxygen is prevented from flowing in, resulting in a decrease in the amount of dissolved oxygen in the water. In this way, fish and aquatic organisms die, a foul odor is generated, and the ecosystem of the water area is destroyed, which causes many social, economic, and environmental problems.
[0005] The above-mentioned green algae are collectively referred to as plants that contain chlorophyll-a and -b like terrestrial plants and are green in color, and mainly live in water by directly converting vegetative cells into reproductive cells or reproductive organs in a simple form. Blue-green algae are prokaryotes that are located between bacteria and algae and have photosynthesis. They can survive on the ground or in water and form various ecosystems. Their phosphorus (P) and nitrogen (N) components play the role of important nutrients.
[0006] Although this algal bloom phenomenon has attracted much public attention due to its aesthetic value and its value as a source of drinking water or agricultural water, experts have slightly different opinions on the cause of the algal bloom. Blue algae, which have a greater impact on this phenomenon, are primary producers and can grow at any time as long as there is appropriate light and nutrients required for photosynthesis and an appropriate water flow rate. Therefore, algal blooms have recently occurred frequently in lakes, rivers, and coasts around the world.
[0007] According to the investigations conducted so far, the causes of algal blooms include nutrients dissolved in water, climate anomalies caused by global warming, mathematical factors, light transmission, changes in predator feeding, and the massive reproduction of microorganisms such as bacteria and viruses. However, since the algal bloom phenomenon is not caused by a certain factor but by the interaction of multiple factors as mentioned above, the main factors for the occurrence of green algae have unexpectedly different manifestations depending on the physical and physicochemical properties of the target water body.
[0008] Therefore, various methods have been tried so far to reduce algal blooms and red tides in lakes, rivers, coastal areas such as cage farms, etc., which are mainly based on physical and chemical methods such as loess and coagulant spreading, in addition to various control methods such as photocatalysis, ultrasonic treatment, ozone treatment, microbial methods, etc., alone or in combination.
[0009] However, most of the conventional methods described above only have temporary effects and have a problem of being too costly compared to the control effect, thus causing considerable secondary damage to the environment.
[0010] In this regard, looking at the existing technology for purifying water quality, Korean Patent No. 10-0807175 discloses a method for preparing bioceramics for water purification, which is characterized by comprising: inoculating photosynthetic bacteria, lactic acid bacteria and yeast in a microbial culture solution containing nutrients to ferment 100 weight percent of natural mineral powder containing 20-30 weight percent of zeolite, 20-30 weight percent of clay or loess and 40-60 weight percent of germanium medical stone to prepare an antioxidant fermentation microbial solution for generating organic acids such as oxalic acid, citric acid, acetic acid, succinic acid and malic acid with antioxidant function, mixing them at a ratio of 15-25 weight parts, and ripening the above-mentioned antioxidant fermentation microbial solution to make it penetrate into the above-mentioned natural mineral powder; forming the mixture of the ripened natural mineral powder and the above-mentioned antioxidant fermentation microbial solution into a specified shape; drying the above-mentioned mixture molded body to remove moisture; and sintering the dried above-mentioned mixture molded body at 500-650°C for 40-80 minutes.
[0011] Furthermore, the same patent No. 10-0836527 relates to a technology for using a composition for removing red tides, green algae and diatoms using a porous nanoparticle titanium dioxide photocatalyst in areas where algae occur, characterized in that the composition comprises: 10 to 90 parts by weight of porous nanoparticle titanium dioxide having an average particle size of 10 to 500 nm and 90 to 10 parts by weight of porous mineral powder having an average particle size of 10 to 100 μm.
[0012] In addition, the same patent No. 10-1658477 provides a method for preparing a floating body for removing green algae / red tides, which includes: a photocatalyst coating solvent preparation step of preparing a coating solvent containing a photocatalyst; a photocatalyst attachment step of coating the above-mentioned photocatalyst on a floating component; a post-treatment step of immersing the floating component coated with the above-mentioned photocatalyst in distilled water for post-treatment; and a photocatalyst coating floating body completion step of removing the above-mentioned floating component from the distilled water and drying it to complete the floating body coated with the photocatalyst. The same patent disclosure No. 10-2020-0127366 records that the floating photocatalyst includes a floating body formed of expanded polystyrene (EPS) having a density lower than that of water and titanium dioxide (TiO2) nanoparticles fixed on the surface of the above-mentioned floating body. This photocatalyst can photodecompose pollutants in a floating state on the water surface.
[0013] On the other hand, the present invention applies the relevant technologies of Patent No. 10-1265292 (a method for preparing a far-infrared radiation solution and a far-infrared radiation article prepared therefrom) and Patent No. 10-1468929 (a masterbatch containing functional substances and a method for preparing the same) held by the applicant, and combines them with titanium dioxide nanotechnology having a photocatalytic effect to prepare an environmentally friendly plastic molding suitable for designing water purification, which can adsorb and decompose organic matter, block the reproduction of bacteria and mold, and reduce algal blooms, thereby completing the present invention.
[0014] [Prior art]
[0015] [Patent Document]
[0016] (Patent Document 1) Korean Patent Gazette No. 10-0807175 (published on February 27, 2008)
[0017] (Patent Document 2) Korean Patent Gazette No. 10-0836527 (published on June 10, 2008)
[0018] (Patent Document 3) Korean Patent Gazette No. 10-1658477 (published on September 22, 2016)
[0019] (Patent Document 4) Korean Patent Publication No. 10-2020-0127366 (published on November 11, 2020) Summary of the invention
[0020] The object of the present invention is to provide a method for preparing a molded body for water purification, which comprises preparing a natural mineral extract in an environmentally friendly manner, preparing a natural mineral-photocatalyst aqueous solution in which titanium dioxide nanopowder having a photocatalytic effect is dispersed, and impregnating the natural mineral extract into the interior of the tissue of a plastic raw material under high temperature and high pressure conditions to prepare a molded body, which is placed on the surface or in water of a lake or reservoir, a lotus pond, a river, an aquarium, a fish farm, a swimming pool, a water purification plant, etc., thereby not only adsorbing and decomposing organic matter and blocking the reproduction of bacteria and molds, but also effectively reducing algal blooms.
[0021] The method for preparing a shaped body for water purification according to the present invention comprises the following steps in sequence: a first step of preparing a natural mineral powder by crushing a natural mineral mixture of 5 to 15 weight percent of loess, 5 to 15 weight percent of volcanic ash, 25 to 35 weight percent of medical stone, 25 to 35 weight percent of porphyry, and 15 to 25 weight percent of tourmaline into a size of less than 325 mesh; a second step of adding purified water at a ratio of 2 to 5 times the total weight of the natural mineral powder prepared in the first step, and grinding the mixture using a ball mill. mill) for 24 to 48 hours, allowing the solid to precipitate, and then separating the transparent supernatant in a colloidal state in which the natural mineral is dissolved in pure water to prepare a natural mineral extract; a third step, dispersing titanium dioxide (TiO2) nanopowder with a particle size of 1 to 100 nm at a ratio of 1 to 10 parts by weight relative to 100 parts by weight of the natural mineral extract prepared in the second step to prepare a natural mineral-photocatalyst aqueous solution; a fourth step, dispersing the natural mineral-photocatalyst aqueous solution prepared in the third step in a high-temperature and high-pressure sealed device in which a plastic raw material with a particle size of 1 to 10 mm is loaded, so that the natural mineral-photocatalyst aqueous solution is impregnated in the structure of the plastic raw material; a fifth step, preparing a plastic molded body of a specified shape from the plastic raw material impregnated with the natural mineral-photocatalyst aqueous solution prepared in the fourth step.
[0022] According to a preferred embodiment of the present invention, it is characterized in that in the above-mentioned fourth step, the natural mineral-photocatalyst aqueous solution is sprayed for 1 to 10 minutes in a sealed device at a temperature of 80 to 120°C and a pressure of 3 to 6 bar, and cooled at room temperature (15 to 25°C), and the plastic molded body formed in the above-mentioned fifth step is formed in a plate-like or hollow spherical form with a specific gravity within the range of 0.9 to 1.5, and the water circulation passage (hole) of the above-mentioned hollow spherical plastic molded body is perforated to within 2 to 6 holes.
[0023] The method for preparing a formed body for water purification according to the present invention has the following effects: a natural mineral extract is prepared in an environmentally friendly manner, heavy metals or foreign matter contained in the mineral itself is not mixed in, and under high temperature and high pressure conditions, a natural mineral-photocatalyst aqueous solution in which titanium dioxide (TiO2) nanopowder is dispersed in the above-mentioned natural mineral extract is impregnated into a plastic raw material, and then cooled at room temperature, so that an aggregate composed of a composite of natural minerals and titanium dioxide components is semi-permanently infiltrated into the tissue of the plastic raw material.
[0024] The water purification molded body prepared as described above is set on the water surface or in the water, and maintains its function for a long time. It not only adsorbs and decomposes organic matter contained in the water and effectively blocks the reproduction of bacteria and molds, but also reduces algal blooms. Therefore, the water purification function can be smoothly performed at a low cost, and the structure and color of the above-mentioned molded body can be designed to match the natural environment, thereby having the advantage of improving the surrounding beauty. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a process flow chart showing a method for producing a shaped body for water purification according to the present invention. DETAILED DESCRIPTION
[0026] The following describes in detail the method for preparing the shaped body for water purification according to the present invention. This is for illustration purposes so that ordinary technicians in the technical field to which the present invention belongs can easily implement the invention, but it does not mean that the technical concept and scope of the present invention are limited thereto.
[0027] like Figure 1As shown, the method for preparing a shaped body for water purification according to the present invention comprises the following steps: a first step, preparing natural mineral powder by crushing a natural mineral mixture of 5 to 15 weight percent of loess, 5 to 15 weight percent of volcanic ash, 25 to 35 weight percent of medical stone, 25 to 35 weight percent of porphyry, and 15 to 25 weight percent of tourmaline into a size of less than 325 mesh; a second step, adding purified water at a ratio of 2 to 5 times the total weight of the natural mineral powder prepared in the first step, and grinding the mixture using a ball mill. mill) for 24 to 48 hours, allowing the solid to precipitate, and then separating the transparent supernatant in a colloidal state in which the natural mineral is dissolved in pure water to prepare a natural mineral extract; a third step, dispersing titanium dioxide (TiO2) nanopowder with a particle size of 1 to 100 nm at a ratio of 1 to 10 parts by weight relative to 100 parts by weight of the natural mineral extract prepared in the second step to prepare a natural mineral-photocatalyst aqueous solution; a fourth step, dispersing the natural mineral-photocatalyst aqueous solution prepared in the third step in a high-temperature and high-pressure sealed device in which a plastic raw material with a particle size of 1 to 10 mm is loaded, so that the natural mineral-photocatalyst aqueous solution is impregnated in the structure of the plastic raw material; a fifth step, preparing a plastic molded body of a specified shape from the plastic raw material impregnated with the natural mineral-photocatalyst aqueous solution prepared in the fourth step.
[0028] Thus, the first step is to prepare a process for natural mineral powder by crushing natural minerals mixed with a ratio of 5-15 weight percent of loess, 5-15 weight percent of volcanic ash, 25-35 weight percent of medical stone, 25-35 weight percent of porphyry, and 15-25 weight percent of tourmaline into a size of less than 325 meshes (about 44 μm). The natural minerals composed of the above-mentioned loess, volcanic ash, medical stone, porphyry, and tourmaline are crushed for the first time in an appropriate ratio into a size of less than 325 meshes (about 44 μm), and harmful substances and heavy metals are easily separated. The above-mentioned natural mineral powder presents a neutral to weak alkalinity of about pH 7-8 as a whole, thereby being prepared as an environmentally friendly raw material that is completely harmless to the human body.
[0029] The above-mentioned loess is composed of about 50-60% silicon dioxide (SiO2), 8-12% aluminum oxide (Al2O3), 2-4% iron oxide (Fe2O3), 0.8-1.1% ferrous oxide (FeO), about 0.5% titanium dioxide (TiO2) and manganese oxide (MnO), 4-16% lime (CaO), 2-6% magnesium oxide (MgO) and other weight ratios. It is reported that this exhibits far-infrared radiation, heavy metal adsorption, antibacterial and deodorizing, and volatile substance removal effects. The research results also revealed that even though the organic matter contained in the loess is relatively poor, the reason why the soil is still fertile is because of the high cation exchange capacity and permeability.
[0030] The above-mentioned volcanic ash refers to particles smaller than 2 to 4 mm in size among volcanic ejecta composed of lava flakes, mineral particles, glass fragments, etc. Volcanic ash is rich in inorganic substances such as potassium, sodium, and phosphorus required for plant growth, and acts as a natural fertilizer. It also has excellent cation exchange capacity and anion generation. It slowly weathers and forms fertile soil that is conducive to plant growth. By utilizing this effect, it can also be used as a cement admixture in the civil engineering field.
[0031] The above-mentioned medical stone (barley stone) belongs to the granite family in geology. Like quartz porphyry, feldspar porphyry and granite porphyry, it is composed of a fine mixture of quartz and feldspar. 3 It is composed of 30,000 to 150,000 pores, has strong adsorption, and contains about 25,000 kinds of inorganic salts. The main components are anhydrous silicate (SiO2) and aluminum oxide (Al2O3), and a small amount of iron oxide (Fe2O3), which plays a role in exchanging heavy metals and ions, so it is also used as a harmful metal remover. It is known that if heat is applied to this rock, far infrared rays are released, and this property is often used in various industrial fields such as saunas and medical equipment.
[0032] The above-mentioned granite is a fine-grained granite, which is a rock showing graphic texture. Graphic texture is shown on the stone tools in the porphyritic rock. This is because the last residual liquid in the crystallization of alkaline magma is formed into crystals, thus contributing to the formation of alkaline natural minerals.
[0033] The above-mentioned tourmaline is mainly produced in pegmatite and metamorphic limestone in contact with granite magma. It is a very rich and developed crystal. Due to its resistance to weathering, it accumulates in detrital deposits. Therefore, in addition to being used as a gem, it is also used in pressure devices by utilizing the property of generating electricity when piezoelectricity, i.e., mechanical force is applied or the shape changes when voltage is applied. In the present invention, in order to improve the cation capture capacity in water, it is mixed at a ratio of 15 to 25 weight percent based on the total weight of natural minerals.
[0034] The natural minerals mixed with the above components are composed in a neutral to weakly alkaline state within pH 7 to 8, which does not cause environmental pollution. The particles are crushed to a size of less than 325 mesh, i.e., about 44 μm or less, to prepare natural mineral powders with excellent far infrared and anion generation and excellent ion exchange (cation substitution ability). The above natural minerals have the effects of heavy metal removal, deep sleep, deodorization, mold growth prevention, water quality and air purification, etc., and are also used as residential and building materials.
[0035] Next, the second step is to add purified water at a ratio of 2 to 5 times the total weight of the natural mineral powder prepared in the first step, grind it using a ball mill for 24 to 48 hours, precipitate the solid, and then separate the colloidal transparent supernatant in which the natural mineral is dissolved in the purified water to prepare a natural mineral extract. This preparation precipitates the heavy metals and foreign matter contained in the natural mineral powder prepared in the first step into a solid and removes it, while at the same time being easily impregnated into the colloidal natural mineral extract of the plastic raw material.
[0036] For the above-mentioned natural mineral extract, the dispersoid (colloid particles, one particle diameter is about 0.1 μm) forms a sol state that maintains fluidity while dispersing pure water as a dispersion medium. When the above-mentioned dispersion medium is water, it is called "hydrosol", and when the above-mentioned dispersion medium is an organic solvent, it is called "organosol". The natural mineral extract obtained from the above-mentioned supernatant is a hydrophilic colloid in a hydrosol state, which adsorbs ions in the aqueous solution as a dispersion medium, or is charged by dissociation of ionizable groups existing on the surface of the particles, and is stabilized by the electrostatic action of this charge, thereby existing in a homogeneous state.
[0037] As mentioned above, the natural mineral powder pulverized by a ball mill has different particle size distributions, but can be separated into a precipitate and a supernatant after settling for about 24 to 48 hours. Of course, the precipitate and the supernatant can also be separated in a short time by a centrifugal separation device. In addition, according to investigations, the particle size of the natural mineral (dispersoid) contained in the above-mentioned colloidal transparent supernatant is within 0.001 to 10 μm (1 to 1000 nm).
[0038] According to research, the large amount of metallic cations contained in the above-mentioned natural minerals (dispersoids) not only exert an ionic adsorption effect on the cell wall of negatively charged green algae, but also play a role in the endocytosis of bacterial cells, using the powerful oxidizing power of the cations that penetrate into the interior of the cells to collapse the cell wall, and inhibit the energy metabolism of the cells by combining with the cysteine group (-SH) of amino acids, which are the structural elements of the cells, and react with the base sequence of the DNA in the cells to inhibit DNA replication (paper source: Antimicrobial Polymers with Metal Nanoparticles-Antibacterial polymers containing metal nanoparticles 2015).
[0039] Furthermore, the pure water (or ultrapure water) used in the present invention refers to distilled tap water or water purified by ion exchange resin. This is a state in which all impurities such as dissolved ions, solid particles, microorganisms, organic matter and dissolved gases contained in the water are removed, thereby improving the cationic content and purity of the natural mineral extract.
[0040] The far infrared radiation rate and radiation energy of the above-mentioned natural mineral extract (based on the total weight of natural minerals mixed with 10 weight ratios of loess, 10 weight ratios of volcanic ash, 30 weight ratios of medical stone, 30 weight ratios of moon porphyry, and 20 weight ratios of tourmaline, and composed of 3 times of pure water) were measured by entrusting the Korea Institute of Infrared Application Evaluation, affiliated with the Korea Far Infrared Association (located at 173, Seokchon-dong, Songpa-gu, Seoul). As a result, it was confirmed that the far infrared radiation rate (5-20 μm) of the black body contrast was 0.893, and the radiation energy (W / m 2 ·μm) is 3.44×10 2 .
[0041] [Table 1]
[0042]
[0043] The third step is to prepare a natural mineral-photocatalyst aqueous solution by dispersing titanium dioxide (TiO2) nanopowder with a particle size of 1 to 100 nm at a ratio of 1 to 10 parts by weight relative to 100 parts by weight of the natural mineral extract prepared in the second step. Titanium dioxide (TiO2), which has been frequently used as a photocatalyst material until now, has the advantages of not only being inexpensive compared to other raw materials, but also having excellent durability and wear resistance as a photocatalyst, and being harmless to the human body and having outstanding stability. In addition, materials that can be used as photocatalysts include ZnO, ZrO2, WO3, perovskite-type composite metal oxides, etc.
[0044] The titanium dioxide (TiO2) remains unchanged even when exposed to sunlight, so it can be used semi-permanently, and has outstanding durability and wear resistance, which is economically advantageous. In addition, it is known that since its oxidizing power is higher than chlorine (Cl2) or ozone (O3), it has outstanding bactericidal power and has the ability to decompose all organic substances into carbon dioxide and water.
[0045] For reference, "photocatalyst" refers to a catalyst that absorbs light and accelerates the speed of photoreaction. That is, when sunlight shines on a substance used as a photocatalyst, such as titanium dioxide (TiO2), electrons (e - ) and holes (made like a belt + The electrons react with oxygen on the surface of the photocatalyst to produce peroxide anions (O2 - ).
[0046] Furthermore, holes react with water to form hydroxyl radicals (neutral OH), which are very capable of oxidatively decomposing organic matter. Therefore, they decompose odorous substances, viruses, bacteria such as microbes, etc. in the air or water and convert them into water and carbon dioxide. Photocatalytic reactions using this effect are often used in purification processes for removing pollutants in the air or water.
[0047] In the field of water treatment in the past, among the methods using titanium dioxide photocatalyst powder, the method using nanometer (nm) sized photocatalyst powder has outstanding efficiency, but it is difficult to recover the photocatalyst powder after water treatment, and there is a problem that an additional recovery process needs to be constructed after the water treatment process. Therefore, a fixation method for fixing the photocatalyst on a carrier has been developed recently. Generally speaking, a fixed type in which the photocatalyst is coated on a glass fiber or a quartz tube, etc., or a flow type in which the photocatalyst is coated on a carrier is applicable.
[0048] However, although fixed photocatalyst carriers are easy to set up and operate, their specific surface area is small and the processing efficiency is reduced, or organic carriers and binders are used to attach the photocatalyst, so there is a problem of the photocatalyst being detached during the oxidation reaction and the carrier and binder decomposing. Micron-sized inorganic hollow particles that support photocatalysts as mobile phase photocatalysts have the disadvantage of requiring too much cost.
[0049] In order to improve this shortcoming, the present invention uses a process in which a natural mineral-photocatalyst aqueous solution obtained by dispersing titanium dioxide (TiO2) nanopowder as a photocatalyst in a colloidal natural mineral extract at a ratio of 1 to 10 parts by weight is impregnated into a plastic raw material, thereby exerting the function of the natural mineral-photocatalyst until the life of its carrier is exhausted, thereby providing a molded body that can adsorb and decompose organic matter in water and block the reproduction of bacteria and molds while reducing algal blooms, that is, a method for preparing a fixed natural mineral-photocatalyst molded body.
[0050] According to research, the content of the above-mentioned titanium dioxide nanopowder is dispersed at a ratio of 1 to 10 parts by weight based on 100 parts by weight of natural mineral extract. As a result, the natural mineral-photocatalyst aqueous solution stably maintains a hydrophilic colloid state in a hydrosol state, and is then effectively impregnated into the internal structure of the plastic raw material, which is suitable for exerting the function of the natural mineral-photocatalyst nanopowder complex.
[0051] The fourth step for realizing the above function is carried out through the following process: the natural mineral-photocatalyst aqueous solution prepared in the third step is sprayed into a high-temperature and high-pressure sealing device which contains plastic raw materials with a particle size of 1 to 10 mm, and the natural mineral-photocatalyst aqueous solution is impregnated into the internal structure of the plastic raw materials.
[0052] Among them, in the above-mentioned fourth step, the natural mineral-photocatalyst aqueous solution is sprayed for 1 to 10 minutes in a sealed device at a temperature of 80 to 120°C and a pressure of 3 to 6 bar, so that the natural mineral-photocatalyst aqueous solution can be effectively impregnated into the internal structure of the plastic raw material with a particle size of 1 to 10 mm, and then cooled at room temperature (15 to 25°C) to remove moisture, thereby agglomerating the natural mineral-photocatalyst nanopowder complex in the above-mentioned plastic principle and semi-permanently fixed (fixed).
[0053] When the above-mentioned plastic raw materials are treated under the conditions of high temperature and high pressure as described above, plastic raw materials with a particle size of 1 to 10 mm are used, which are suitable as a carrier (carrier) for uniformly fixing (fixing) the natural mineral-photocatalyst aqueous solution in the raw materials. The present invention adjusts its particle size distribution and the process conditions of the sealing equipment within the specified range, thereby maximizing the impregnation amount of the natural mineral-photocatalyst aqueous solution. Therefore, the specific type of the above-mentioned plastic raw materials themselves is not strictly limited.
[0054] However, in the present invention, as resins that can change their shape with the help of heat, crystalline thermoplastic resins such as polyethylene (HDPE, LDPE, etc.), polypropylene (PP), nylon (Nylon), polyacetal, etc. and non-crystalline thermoplastic resins such as polyvinyl chloride resin (PVC), polystyrene (PS), ABS resin, acrylic resin, etc. are used, and their efficacy has been confirmed to have good workability and reduce production costs, and the fact that a high concentration of a natural mineral-photocatalyst aqueous solution can be easily impregnated inside the structure of the plastic raw material, that is, between the polymer segments.
[0055] The final fifth step is a process for preparing a plastic molded body of a specified shape from the plastic raw material impregnated with the natural mineral-photocatalyst aqueous solution prepared in the fourth step. The thermoplastic resin as described above is selectively used to form a plate-like or hollow spherical shape with a specific gravity within the range of 0.9 to 1.5. Thus, the water purification molded body is stably set on the water surface or in the water and maintains the function for a long time. Thus, the water purification function can be well exerted even at a low cost. The structure and color of the molded body are then designed to match the natural environment, thereby improving the surrounding beauty.
[0056] The above-mentioned hollow spherical plastic molded body is named "GREEN BAL L", which means that it performs the function of purifying the hydrosphere in the natural environment. Its surface is perforated with 2 to 6 water circulation passages (holes), thereby making the water circulation inside and outside the hollow ball smooth, promoting the adsorption and decomposition of organic matter, blocking the reproduction of bacteria and molds, and preventing algal blooms, thereby improving the water purification function, and it is easy to achieve mutual connection between the above-mentioned molded bodies, thereby forming a molded body structure with a unique shape.
[0057] As described above, although the water purification molded body prepared by the present invention is completed through a number of experiments, the present invention is described below through preferred embodiments that can be easily understood and implemented by ordinary technicians in this technical field.
[0058] [Example]
[0059] The first step is to grind the natural minerals of loess, volcanic ash, medical stone, porphyry and tourmaline into particles of 325 mesh (about 44 μm) at a ratio of 10, 10, 30, 30 and 20 weight percent respectively.
[0060] The second step: 300 parts by weight of pure water as a solvent is added to 100 parts by weight of the natural mineral powder prepared in the first step, and the powder is pulverized by a ball mill for 48 hours to allow the solid to precipitate. Then, a colloidal transparent supernatant in which the natural mineral is dissolved in the pure water is separated to prepare a natural mineral extract.
[0061] The third step: relative to 100 parts by weight of the natural mineral extract prepared in the second step, 5 parts by weight of titanium dioxide (TiO2) nanopowder with a particle size of 1 to 100 nm is dispersed to prepare a natural mineral-photocatalyst aqueous solution.
[0062] Step 4: In a high-temperature and high-pressure (temperature 95°C and pressure 3 bar) sealed device filled with plastic raw materials (HDPE resin) with a particle size of 1 to 10 mm, the natural mineral-photocatalyst aqueous solution prepared in the third step is sprayed for 5 minutes. After the natural mineral-photocatalyst aqueous solution is impregnated into the internal structure of the plastic raw material, it is cooled at room temperature.
[0063] The fifth step is to form a plastic raw material (HD PE resin) impregnated with the natural mineral-photocatalyst aqueous solution prepared in the fourth step into a spherical shape with a diameter of 25 to 28 cm and a thickness of 3 mm to prepare a water purification molded body (green ball) with four water circulation channels perforated and a diameter of 7.5 cm.
[0064] [Experimental Example 1]
[0065] The test results of evaluating the algae removal efficiency of the water purification molded body prepared in the above example are shown in the following [Table 2].
[0066] [Table 2]
[0067]
[0068] ○Test method: Based on the Ministry of Environment Regulation No. 697, Appendix 1 "Algae removal efficiency and ecotoxicity evaluation method".
[0069] ○ Usage concentration: Total weight of the fragments put in, weight of 12 fragments (average area of 1 fragment: 38.47cm 2 ).
[0070] As shown in the test results of [Table 2] above, the molded article for water purification prepared by the method of the present invention showed an effectiveness of reducing the number of algae cells (cells / mL) by 91% after 24 hours and 97% after 72 hours, and the algae growth inhibition rate exceeded 100%. On the contrary, the control group showed a phenomenon of an increase of about 23 times in the number of algae cells after 72 hours of the test.
[0071] [Experimental Example 2]
[0072] The test results of the ecotoxicity evaluation of the molded body for water purification prepared in the above-mentioned example are shown in the following [Table 3], and it was found that the molded body has no toxicity to the ecological system.
[0073] [Table 3]
[0074]
[0075] ○Usage concentration: 1053cm 2 / L(1Fragment average surface area: 79.0cm 2 , average weight of 1 fragment: 5.6g)
[0076] [Experimental Example 3]
[0077] In order to conduct a water quality improvement demonstration test of the Korean Agricultural and Fishery Village Corporation on the water purification molded body prepared in the above embodiment, the above molded body structure was set up in the Geumbong Reservoir located in Gimpo-ri, Nongong-eup, Dalseong-gun, Daegu Metropolitan City. The test results are shown in the following [Table 4].
[0078] [Table 4]
[0079] distinguish Before Setup 1 month later 2 months later 3 months later 4 months later 5 months later <![CDATA[Chl-a(mg / m 3 )]]> 101.4 44.1 52.5 86.4 17.2 68.5 TOC(mg / L) 9.5 4.7 6.7 6.5 5.4 6.7
[0080] ○Chl-a concentration: the existing amount of total algae (chlorophyll).
[0081] ○TOC: Total Organic Carbon (TOC) expresses the amount of all oxidizable organic compounds in water as carbon.
[0082] From the test results in [Table 4] above, it can be confirmed that the water purification molded body according to the preparation method of the present invention can obtain a water quality improvement effect of Chl-a 56% and TOC 51% when it is set for 1 month. During the 5-month test bench period, the water quality improvement effect of an average Chl-a of 51% and TOC of about 34% is shown. For the above-mentioned water purification molded body, the natural mineral-photocatalyst nanopowder complex is agglomerated in the plastic raw material and semi-permanently fixed (fixed), thereby reducing the occurrence of algal blooms for a long time.
[0083] Therefore, the water purification molded body prepared according to the present invention can be used in a variety of purposes and forms without departing from the technical idea of the present invention in order to purify the sea surface caused by red tide (a phenomenon in which the seawater turns red due to the explosive growth of specific algae), in addition to reducing the algal bloom phenomenon by adsorbing and decomposing organic matter contained in the water of lakes or reservoirs, lotus ponds, rivers, aquariums, aquaculture farms, swimming pools, water treatment plants, etc. and blocking the reproduction of bacteria and molds.
Claims
1. A method for preparing a shaped body for water purification, characterized in that: The steps are as follows: The first step is to prepare natural mineral powder by crushing natural minerals mixed in a ratio of 5-15 weight percent of loess, 5-15 weight percent of volcanic ash, 25-35 weight percent of medical stone, 25-35 weight percent of porphyry, and 15-25 weight percent of tourmaline into particles with a size of less than 325 mesh; The second step is to add purified water at a ratio of 2 to 5 times the total weight of the natural mineral powder prepared in the first step, and grind it by a ball mill for 24 to 48 hours to allow the solid to precipitate, and then separate the colloidal transparent supernatant in which the natural mineral is dissolved in the purified water to prepare a natural mineral extract; The third step is to prepare a natural mineral-photocatalyst aqueous solution by dispersing titanium dioxide (TiO2) nanopowder having a particle size of 1 to 100 nm at a ratio of 1 to 10 parts by weight relative to 100 parts by weight of the natural mineral extract prepared in the second step; The fourth step is to disperse the natural mineral-photocatalyst aqueous solution prepared in the third step into a high-temperature and high-pressure sealed device filled with a plastic raw material with a particle size of 1 to 10 mm, and impregnate the natural mineral-photocatalyst aqueous solution into the structure of the plastic raw material; In the fifth step, the plastic raw material impregnated with the natural mineral-photocatalyst aqueous solution prepared in the fourth step is prepared into a plastic molded body of a predetermined shape.
2. The method for preparing a shaped body for water purification according to claim 1, characterized in that: In the fourth step, the natural mineral-photocatalyst aqueous solution is sprayed for 1 to 10 minutes in a sealed device at a temperature of 80 to 120° C. and a pressure of 3 to 6 bar, and then cooled at a room temperature of 15 to 25° C.
3. The method for preparing a shaped body for water purification according to claim 1, characterized in that: The plastic molded body formed in the fifth step is formed in a plate-like or hollow spherical form having a specific gravity of 0.9 to 1.
5.
4. The method for preparing a shaped body for water purification according to claim 3, characterized in that: The surface of the hollow spherical plastic molding is perforated with 2 to 6 water circulation passages.
5. A molded body for water purification, characterized in that: The shaping is performed by the production method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Bio-ceramic for water purification and manufacturing method thereof
KR100807175B1
Float for controlling green algae and red algae and manufacturing method thereof
KR101658477B1
Floating photocatalyst and method of manufacturing the floating photocatalyst
KR1020200127366A
Medical stone and tourmaline mineralization water dispenser
CN102491580A
Far infrared ray radiator used for non-contact water purification, preparation method, and water purification device
CN108002806A